Increasing Confidence and Ability in Implementing Kangaroo Mother Care Method Among Young Mothers. (30th November 2017) - Kenanga Purbasary, Eleni; Rustina, Yeni; Budiarti, Tri
ABSTRACT: Mothers giving birth to low birth weight babies (LBWBs) have low confidence in caring for their babies because they are often still young and may lack the knowledge, experience, and ability to care for the baby. This research aims to determine the effect of education about kangaroo mother care (KMC) on the confidence and ability of young mothers to implement KMC. The research methodology used was a controlled-random experimental approach with pre- and post-test equivalent groups of 13 mothers and their LBWBs in the intervention group and 13 mothers and their LBWBs in the control group. Data were collected via an instrument measuring young mothers' confidence, the validity and reliability of which have been tested with a resulting r value of .941, and an observation sheet on KMC implementation. After conducting the education, the confidence score of young mothers and their ability to perform KMC increased meaningfully. The score of confidence of young mothers before education was 37 ( p = .1555: and the ability score for KMC Implementation before education was 9 ( p = .1555). The median score of confidence of young mothers after education in the intervention group was 87 and in the control group was 50 ( p = .001, 95% CI 60.36–75.56), and ability median score for KMC implementation after education in the intervention group was 16 and in the control group was 12 ( p = .001, 95% CI 1.50–1.88). KMC education should be conducted gradually, and it is necessary to involve the family, in order for KMC implementation to continue at home. A family visit can be done for LBWBs to evaluate the ability of the young mothers to implement KMC.